Spotlight - Minerals Engineering '93 Conference, Cape Town, South Africa, 25 To 27 August 1993 (The Southern African Institute of Mining and Metallurgy, 1993)
For the past 12 years, the Universities of Stellenbosch and Cape Town have hosted an annual symposium to discuss research topics in Minerals Processing. Since 1987, this meeting has been held under the auspices of the Western Cape Branch of the South African Institute of Mining and Metallurgy, and has enjoyed much national and international support. In 1993, in place of the usual Symposium, the Branch and Universities collaborated with CSM Associates Ltd and Minerals Engineering Journal is organizing the international Minerals Engineering '93 Conference in Cape Town.